Pharmaceutical representative activities in Benin and Ghana : promoting firms while helping construct the pharmaceutical economy of African countries - (:unkn) unknown (My University, 2021)
In West Africa, the activities of sales representatives used by the pharmaceutical industry are organized according to the legal dispositions, with great differences between French-speaking and English-speaking countries. Thus, in Ghana, where distributors have the legal right to represent firms and promote their products, except for the Big Pharma, it is these distributors who ensure the trade through a large majority of sales reps and a few medical reps. In Benin, where the distribution activity is legally separate from that of promotion, we are seeing the emergence of a growing number of representative agencies, which have supplanted the direct-lab employed directly by the firms. But here too a distinction is made between Big Pharma, represented by international agencies, and Asian and African producers represented by smaller, local agencies with fewer resources. Based on governmental regulation and the country's pharmaceutical distribution structure, the firms develop territorial and therapeutic strategies: segmentation in Ghana, concentration in Benin. But similar strategies appear in how the end users are targeted based on their financial situation. It combines to varying degrees scientific promotion and purely commercial strategies. Beyond the firms, in both countries, sales representatives appear to generate definite and endogenous pharmaceutical dynamics in their country.
Keywords: African Research